Loading of CAR‐T cells with magnetic nanoparticles for controlled targeting suppresses inflammatory cytokine release and switches tumor cell death mechanism - Pfister, Felix; Carnell, Lucas; Löffler, Lisa; Boosz, Philipp; Schaft, Niels; Dörrie, Jan; Stein, René; Lenz, Malte; Spiecker, Erdmann; Huber, Christian; Haddadin, Sami; Berking, Carola; et al. (MedComm, 2025)
Therapies against hematological malignancies using chimeric antigen receptors (CAR)-T cells have shown great potential; however, therapeutic success in solid tumors has been constrained due to limited tumor trafficking and infiltration, as well as the scarcity of cancer-specific solid tumor antigens. Therefore, the enrichment of tumor-antigen specific CAR-T cells in the desired region is critical for improving therapy efficacy and reducing systemic on-target/off-tumor side effects. Here, we functionalized human CAR-T cells with superparamagnetic iron oxide nanoparticles (SPIONs), making them magnetically controllable for site-directed targeting. SPION-loaded CAR-T cells maintained their specific cytolytic capacity against melanoma cells expressing the CAR-specific antigen chondroitin sulfate proteoglycan (CSPG4). Importantly, SPIONs suppressed cytokine release in the loaded CAR-T cells, shifting the cell death phenotype in the tumor cells from pyroptosis to apoptosis. Furthermore, SPION-loaded CAR-T cells could be enriched in a dynamic flow model through an external magnetic field and be detected in MRI. These results demonstrate that lytic cytotoxicity is retained after SPION-functionalization and provides a basis for future site-specific immunotherapies against solid tumors with reduced systemic adverse side effect